Cultivating change: an evaluation of departmental readiness for faculty diversification - Carter-Veale, Wendy Y.; Cresiski, Robin H.; Sharp, Gwen; Lankford, Jordan D.; Ugarte, Fadel (Frontiers in Education, 2025)
Despite the increasing number of racially and ethnically minoritized (REM) individuals earning PhDs and the substantial investment in diversity initiatives within higher education, the relative lack of diversity among faculty in tenure-track positions reveals a persistent systemic challenge. This study used an adaptation of the Community Readiness Tool to evaluate readiness for faculty diversification efforts in five biomedical departments. Interviews with 31 key informants were transcribed and coded manually and using NVIVO 12 in order to assign scores to each department in the six domains of readiness. The results revealed no meaningful differences in overall scores across institutional types, but did show differences within specific domains of readiness. These findings indicate that readiness is multi-faceted and academic departments can benefit by identifying priority areas in need of additional faculty buy-in and resources to enhance the success of diversification efforts.